Indonesian public officials after erroneous statements about COVID-19: An application of image restoration theory - Andarini, Rindang Senja; Pratiwi, Miftha; Setiyowati, Rini; Santoso, Anang Dwi (Frontiers in Political Science, 2023)
Introduction This study aimed to examine the tactics and strategies of Indonesian public officials to restore their reputation after making false claims and policies on coronavirus 2019 (COVID-19). The significance of this study can be separated into two categories. First, the application of image restoration theory to public organizations and public officials is uncommon. Second, it is essential to analyze the application of this theory to diverse social, political, and economic contexts of emerging nations; as a result, these distinctions may lead to varied research conclusions. Methodology A dataset of 2,000 Instagram posts by Indonesian public officials was generated to conduct the content analysis. Results This study found that reducing offensiveness, evading responsibility, and taking corrective action are the three most commonly seen practices followed by Indonesian public officials. This study confirms that denial and mortification are employed exceedingly infrequently in non-Western countries because both these strategies are believed to diminish the image of public leaders in public view. Discussion This study presents the practical implications that public officials or public relations experts who represent them must be cautious since it can have severe implications on their reputation. This study also argues that erroneous claims when posted by public officials attract unwanted public attention and negatively affect their image. Furthermore, this study provides practical implications for public officials and their representatives to be more cautious while handling media accounts.